IDENTIFIKASI KAWASAN PELUANG PEMENUHAN TARGET RUANG TERBUKA HIJAU 30% DI DKI JAKARTA - Andriani, Susi; Waryono, Tarsoen; Thayib, Mohammad Hasroel (Bumi Lestari, 2016)
The research was conducted on 3 components of Green Open Space (GOS) in Jakarta, namely landscaping, agriculture and forestry. The research objective was to determine the distribution and  extensive of Existing Green Open Space in Jakarta in 2012, and to identify the potential opportunity areas to fulfill the target of 30% GOS in Jakarta. Search distribution is done with Landsat TM imagery aids Band 54 corrected in 2011 by analyzing the vegetation index values   (NDVI). Search area opportunity to meet the target of 30% was the buffer zone (river banks, beaches and water tanks), as well as the areas that have awakened to meet the obligation Law. 26 of 2007. The results showed the existing green open space in Jakarta in 2012 was 7,842.61 ha (13.27%) of the total land area of Jakarta. realization Landscaping recorded 2,718.37 ha, 1,950.08 ha Forestry, and Agriculture 2,813.29 ha . The opportunity potential areas to fulfill the target recorded more of 10,003.92 ha.
Keywords: green open spaces, expansive and distribution, areas opportunities, jakarta